Biological prerequisites for the introduction of health-saving technologies in the process of adaptive physical education of schoolchildren with visual impairments - Bozhena Bukhovets; Galyna Dyshel; Petro Todorov; Inna Asauliuk; Vitaly Usychenko (Фізична реабілітація та рекреаційно-оздоровчі технології)
Purpose. The purpose of the presented scientific research was, based on factor analysis, to substantiate the biological prerequisites for the introduction of health-saving technologies in the process of adaptive physical education of schoolchildren with visual impairments.